2008
DOI: 10.5117/9789053568941
|View full text |Cite
|
Sign up to set email alerts
|

International Migration in Europe : New Trends and New Methods of Analysis

Abstract: corrado bonifazi, marek oklski, jeannee schoorl & arick simon (eds.)A m s t e r d a m U n i v e r s i t y P r e s s RESEARCH imiscoe International Migration in Europe IMISCOE (International Migration, Integration and Social Cohesion) IMISCOE is a Network of Excellence uniting over 500 researchers from various institutes that specialise in migration studies across Europe. Networks of Excellence are cooperative research ventures that were created by the European Commission to help overcome the fragmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 30 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…This is not the case for international migrants, in particular those born abroad (first generation) (Bonifazi 2008). Something similar can be said in regard to the comparison between movers and stayers: most of the recent work on the occupational and social careers of migrants is unable make a judgement as to whether migration was a good choice because the data does not allow comparison between the outcomes of migrants and of their peers who remain in the home country.…”
Section: Introductionmentioning
confidence: 99%
“…This is not the case for international migrants, in particular those born abroad (first generation) (Bonifazi 2008). Something similar can be said in regard to the comparison between movers and stayers: most of the recent work on the occupational and social careers of migrants is unable make a judgement as to whether migration was a good choice because the data does not allow comparison between the outcomes of migrants and of their peers who remain in the home country.…”
Section: Introductionmentioning
confidence: 99%
“…The goal is not to dissolve migrants in new cultures but to keep their national identity, being at the same time loyal to the hosting culture and active when entering new social systems. However, some authors concluded after some time that the model of multiculturalism actually had not achieved the necessary goals or implemented this model adaptation's potential (Bonifazi, Schoorl, Okólski, & Simon, 2008;Sam, Vedder, Leibkind, Neto, & Virta, 2008;Silj, 2010). The paradox was that social securities, including social allowances issued to migrants, instead of stimulating them to active integration, promoted the first generation's passive position and marginalization.…”
mentioning
confidence: 99%